PENINGKATAN KAPASITAS KEMITRAAN UNTUK MENDORONG RANTAI NILAI KOMODITAS KOPI YANG BERKELANJUTAN (Forum Penelitian Agro Ekonomi, 2023)
Coffee is one of the world's most traded agricultural commodities, but sustainability in its value chain remains an issue. While governments, companies, and non-governmental organizations (NGOs) play a strategic role in the value chain, the gatekeepers of sustainability, namely coffee farmers, have a weak position. Cross-sector partnerships have the potential to serve as an innovative mechanism to address sustainability issues in coffee value chains by changing the relationships between key actors in the chain to make them more equitable and mutually beneficial. However, the capacity of partnerships to do this empirically is still unknown, especially when linked to the farmer context. This paper uses a literature review method to analyze partnership capacity from the perspectives of governance and development studies. The results of the review show that the governance perspective sees partnerships as initiators and agents of change in the coffee value chain. On the other hand, the development perspective critically views partnerships driven by businesses and NGOs still having ambiguous impacts on farmers. As part of the neoliberal agenda, partnership seems unable to provide solutions to various gaps in the coffee value chain. Thus, the partnership needs to be improved by adopting a more inclusive business model that involves all stakeholders and is built with a bottom-up perspective that considers the local situation and context.
Keywords: certification; coffee; governance; partnership; standardization; value chain; kemitraan; kopi; rantai nilai; standardisasi; sertifikasi; tata kelola